Frequency of apical periodontitis in root‐filled teeth restored with post and core: A 5‐year retrospective study - Louise Johansson; Jakob Jonsson Sjögren; Anders Wirén; Alf Eliasson; Fredrik Frisk (Wiley, 2024)
Abstract Background In conjunction with post placement in root‐filled teeth with periapical healthy conditions, root canal retreatment may be performed to improve the seal of the root canal. Whether root canal retreatment for technical reasons (retreatments in teeth without apical periodontitis (AP)) results in lower frequency of AP is unknown. Objective To examine whether there is a difference in frequency of AP between roots with root canals retreated for technical reasons, and roots with root canals not retreated before post placement, with a minimum follow‐up of 5 years. Also, to examine changes in root filling quality following root canal retreatment for technical reasons. Methods This retrospective study included radiographs of 441 root‐filled roots without periapical radiolucencies at baseline, scheduled for post and core treatment. Follow‐up data for a minimum of 5 years were available for 305 roots (loss to follow‐up 30.8%), 46 of which were retreated for technical reasons. Two calibrated observers assessed root filling sealing quality and length, respectively, and periapical status according to the Periapical Index. The main outcome of the study, AP, was used as the dependent variable and all analyses were performed at root level. Results The overall frequency of AP at follow‐up was 13.8%. The difference in frequency of AP between retreated (4.3%) and nonretreated (15.4%) root canals was not statistically significant, p = .061. Analyses including only roots with preoperatively inadequate root filling quality showed a statistically significant difference (p = .017) between the two treatment groups (2.4% vs. 22.9%). Conclusions Root canal retreatment for technical reasons before post and core placement significantly reduces the frequency of AP in roots with inadequate root filling quality.